Roman public libraries - Nicholls, M; Nicholls, Matthew Charles (2005)
﻿ This thesis aims to investigate the development and functions of public libraries in Rome and the Roman world. After a preface with maps of libraries in Rome, Section I discusses the precursors for public library provision in the private book collections of Republican Rome, and their transfer into the public domain with the first public libraries of Asinius Pollio and Augustus. Section II contains three 'case studies' of public libraries' different roles. The Augustan library programme is used in Ch.II.l to examine the role of imperial public libraries in literary life and the connections between Rome's libraries and those of Alexandria. Chapter II.2 concentrates on the libraries of Trajan's Forum to explore the intersection of imperial public libraries and monumental public architecture. This chapter responds to an important recent article by arguing for the continued identification of the Forum's libraries with twin brick buildings at its northern end, and suggests a series of correspondences between these libraries and its other monumental components. The conclusions of this chapter are important when considering the public libraries of the wider empire, several of which seem to have been inspired by the Trajanic libraries. Chapter II.3 considers imperial public libraries and leisure by looking at the evidence for libraries within bath-house complexes, concluding that their presence there is consistent with the archaeological and epigraphic evidence and fits in well with what we know of the intellectual and cultural life of these structures. Section III examines various aspects of the practical function of Roman public libraries: their contents (books and archives), division into Latin and Greek sections, provisions for shelving and cataloguing, staff, usership, architectural form, decoration, and housing of works of art. The picture that emerges is of carefully designed and functional buildings intended to sustain public, monumental, and practical functions. Section IV uses a variety of texts to examine the way in which libraries were viewed and used. Ch. IV. 1 discusses the evidence for use of libraries by scholars and authors such as Gellius, Galen, Josephus, and Apuleius. Ch. IV.2 examines parallels between library collections and compendious encyclopaedic elements within Roman literature and considers how library collections came to be canon-forming institutions and vehicles for the expression of imperial approval or disapproval towards authors. The channels through which this imperial influence flowed are investigated in Ch. IV.3, which looks at the directors and staff of the public libraries of Rome. The final section (V) of the thesis concerns public libraries outside the city of Rome. Provincial libraries provide a useful case study in 'Romanisation': they reveal a range of influences and are shown to embody local, personal, and metropolitan imperial identities. There follows a brief conclusion, and a bibliography. There are also five appendices of numismatic and epigraphic material discussed in the text. This material has not been adequately or completely gathered elsewhere and is intended to assist the reader; where appropriate it includes illustrations, transcriptions, and translations.